Comparing measurements of head motion and centre of pressure for body sway induced by optic flow on a head-mounted display - Ashida, Hiroshi; Fujimoto, Kanon (Frontiers in Virtual Reality, 2022)
We compared two measures of visually induced body sway—head motion and centre of pressure (CoP)—that were simultaneously measured while observing optic flow on a head-mounted display (HMD). Head motion can be conveniently tracked with HMDs, but may have some features different from those of conventional CoP measurements, because of the complex joint structures of the human body. In this analysis, the responses were very similar (except for response gain), and we did not find any significant differences in time or frequency domains. Our results support the use of head motion as a potential predictor of variability in body sway, at least in studies of visually guided postural control.